The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1590/1678-4324-2023210792
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fluoxymesterone on Sex Proportion and Growth Performance of Nile Tilapia (Oreochromis niloticus L.).

Abstract: One of the main problems to be solved in the commercial production of Nile tilapia is the use of large volumes of steroids during the sex reversion process. The precise evaluation of the time after hatching to start the steroid treatment could help reduce its use in the short-term. The main objective of this work was to evaluate the sex proportion and the growth obtained in a mixed population of Nile tilapia fed fluoxymesterone at different days (3, 6, 9, 12, and 15) after hatching. A one-factor experiment wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 44 publications
(62 reference statements)
0
0
0
Order By: Relevance
“…However, considering that the lower value of final survival was observed in the group supplemented with only FM at 20 mg per kg, adding the commercial blend might have helped reduce the steroid's negative effects on survival. Although FM is not considered a steroid with strong negative effects (Ramírez-Ochoa et al 2023) on survival, our work showed that at a concentration of 20 mg kg -1 , it caused a decrease in the percentage of survival at the end of the experiment. Several authors have reported in Nile tilapia and its hybrids survival rates lower than those obtained in the present study, ranging from 24 to 83% for fish exposed to 17α-methyltestosterone and similar steroids through feeding (21 to 30 days) (Carranza 1990, Pérez 2002, Pinza-Pinza 2014 or immersions (López et al 2007, Miranda-Cerritos et al 2008, Botero et al 2011.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…However, considering that the lower value of final survival was observed in the group supplemented with only FM at 20 mg per kg, adding the commercial blend might have helped reduce the steroid's negative effects on survival. Although FM is not considered a steroid with strong negative effects (Ramírez-Ochoa et al 2023) on survival, our work showed that at a concentration of 20 mg kg -1 , it caused a decrease in the percentage of survival at the end of the experiment. Several authors have reported in Nile tilapia and its hybrids survival rates lower than those obtained in the present study, ranging from 24 to 83% for fish exposed to 17α-methyltestosterone and similar steroids through feeding (21 to 30 days) (Carranza 1990, Pérez 2002, Pinza-Pinza 2014 or immersions (López et al 2007, Miranda-Cerritos et al 2008, Botero et al 2011.…”
Section: Discussionmentioning
confidence: 58%
“…At the end of the experiment, a higher growth was observed in the treatments that received the commercial blend or FM compared to that recorded in the control group. Previous reports, in terms of reproduction, sex reversal, and growth effects of FM in Nile tilapia (Moreno-Enríquez et al 2003, Torres-Hernández et al 2010, Ornelas-Luna et al 2017, Trejo-Quezada et al 2021, have concluded that, although it does not have a clear and powerful anabolic effect as 17αmethyltestosterone does (El-Saidy et al 2005, Abdelghany 2010, Hafeez-ur-Rehman et al 2014, Ajiboye et al 2015, Trejo-Quezada et al 2021), FM has shown, in some instances, a positive effect on growth at the end of the sex-reversal process (Manosroi et al 2004, Gutiérrez-Sigueros et al 2018, Ramírez-Ochoa et al 2023. Ramírez-Ochoa et al (2023) reported that FM withdrawal caused a growth depression in Nile tilapia juveniles.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations